The Structure of Adamantane Clusters: Atomistic vs. Coarse-Grained Predictions From Global Optimization - Hernández-Rojas, Javier; Calvo, Florent (Frontiers in Chemistry, 2019)
Candidate structures for the global minima of adamantane clusters, (C_10H_16)_N, are presented. Based on a rigid model for individual molecules with atom-atom pairwise interactions that include Lennard-Jones and Coulomb contributions, low-energy structures were obtained up to N=42 using the basin-hopping method. The results indicate that adamantane clusters initially grow accordingly with an icosahedral packing scheme, followed above N=13 by a structural transition toward face-centered cubic structures. The special stabilities obtained at N=13, 19, and 38 are consistent with these two structural families, and agree with recent mass spectrometry measurements on cationic adamantane clusters. Coarse-graining the intermolecular potential by averaging over all posible orientations only partially confirm the all-atom results, the magic numbers at 13 and 38 being preserved. However, the details near the structural transition are not captured well, because despite their high symmetry the adamantane molecules are still rather anisotropic.